(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Grammatical and lexicographic studies based on the corpus, the main tasks and linguistic issues facing the corpus linguistics are reflected in this article.